1999
DOI: 10.1177/0148607199023003117
|View full text |Cite
|
Sign up to set email alerts
|

Oral and Parenteral Glutamine in Bone Marrow Transplantation: A Randomized, Double‐Blind Study

Abstract: Oral and parenteral GLN seemed to be of limited benefit for patients having AUTO or ALLO BMT for hematologic or solid malignancies. Further study of long-term effects of GLN in BMT seems warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(80 citation statements)
references
References 20 publications
0
76
0
4
Order By: Relevance
“…In order to achieve this the glutamine needed to be mixed in 100 ml of sterile water per 10 g of Lglutamine. This corresponds to the dilution used by Schloerb and Skikne (1999). The maximum acceptable volume of suspension was 300 ml in the larger patients taking the higher doses of glutamine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to achieve this the glutamine needed to be mixed in 100 ml of sterile water per 10 g of Lglutamine. This corresponds to the dilution used by Schloerb and Skikne (1999). The maximum acceptable volume of suspension was 300 ml in the larger patients taking the higher doses of glutamine.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamine added to parenteral nutrition has been shown to help prevent intestinal atrophy and to maintain gut integrity (Tremel et al, 1994;van der Hulst et al, 1993). Studies in adult oncology patients have shown that glutamine given orally is well tolerated (Skubitz & Anderson, 1996;Jebb et al, 1995;Schloerb & Skikne, 1999). In one such study a significant decrease in the severity of chemotherapy induced stomatitis was seen using a 'swish and swallow' technique (Skubitz & Anderson, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, the search has produced seventeen (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) randomised controlled trials, of which seven used oral glutamine (22)(23)(24)(25)(26)(27)(28) and ten used intravenous glutamine (29)(30)(31)(32)(33)(34)(35)(36)(37)(38) . Five studies investigated autologous transplantation (24,26,30,32,33) while four investigated allogeneic transplantation (27,29,34,38) and seven were mixed transplant types (22,23,25,28,31,35,37) . Considerabl...…”
Section: Bone-marrow Transplantationmentioning
confidence: 99%